Design of TCM decoder for accurate detection on AWGN and Rayleigh environments - B.Salih, Arshad; Esam Kamal, Ayoub; Shakor Mahmood, Zuhair (International Journal of Engineering and Technology, 2019)
Wireless communications are made an expanded growth during the last decade. Channel is importantly considerable in communication studies where signals are fading and attenuated due to channel disturbances. Todayâ€™s technologies are completely relying on digital signals by adapting devices which understand only digital representation of data. Such techniques shrink the energy required to operate the devices and reduced the cost of deploying such systems in personal and industrial fields. Encryption of data and preparing the signal with good immunity for noise are the main subjects in this paper. Design of Trellis Coding Modulation (TCM) where digital signal can be encoded and modulated at the same paradigm will be illustrated. Decoder of TCM will be deigned to retrieve the original transmitted signal over AWGN and Rayleigh channel with minimum error.Â